Increase in beta frequency phase synchronization and power after a session of high frequency repetitive transcranial magnetic stimulation to the primary motor cortex - Enrico De Martino; Adenauer Girardi Casali; Bruno Andry Nascimento Couto; Thomas Graven-Nielsen; Daniel Ciampi de Andrade (Neurotherapeutics)
High-frequency repetitive transcranial magnetic stimulation (rTMS) to the primary motor cortex (M1) is used to treat several neuropsychiatric disorders, but the detailed temporal dynamics of its effects on cortical connectivity remain unclear. Here, we stimulated four cortical targets used for rTMS (M1; dorsolateral-prefrontal cortex, DLPFC; anterior cingulate cortex, ACC; posterosuperior insula, PSI) with TMS coupled with high-density electroencephalography (TMS-EEG) to measure cortical excitability and oscillatory dynamics before and after active- and sham-M1-rTMS. Before and immediately after active or sham M1-rTMS (15 ​min, 3000 pulses at 10 ​Hz), single-pulse TMS-evoked EEG was recorded at the four targets in 20 healthy individuals. Cortical excitability and oscillatory measures were extracted at the main frequency bands (α [8–13 ​Hz], low-β [14–24 ​Hz], high-β [25–35 ​Hz]). Active-M1-rTMS increased high-β synchronization in electrodes near the stimulation area and remotely, in the contralateral hemisphere (p ​= ​0.026). Increased high-β synchronization (48–83 ​ms after TMS-EEG stimulation) was succeeded by enhancement in low-β power (86–144 ​ms after TMS-EEG stimulation) both locally and in the contralateral hemisphere (p ​= ​0.006). No significant differences were observed in stimulating the DLPFC, ACC, or PSI by TMS-EEG. M1-rTMS engaged a sequence of enhanced phase synchronization, followed by an increase in power occurring within M1, which spread to remote areas and persisted after the end of the stimulation session. These results are relevant to understanding the M1 neuroplastic effects of rTMS in health and may help in the development of informed rTMS therapies in disease.